Sunlight-stimulated phenylalanine ammonia-lyase (PAL) activity and anthocyanin accumulation in exocarp of 'Mahajanaka' mango - Kobkiat Saengnil (2018)
The activity of phenylalanine ammonia-lyase (PAL) required for anthocyanin synthesis was stimulated by sunlight exposure resulting in the development of red colour in 'Mahajanaka' mango exocarp, which occurred only on the sunlight-exposed side of the fruit. The accumulation of anthocyanin was concurrent with the increase in PAL activity in the mature stage of the fruit. The exposed side of the fruit had higher PAL activity, endogenous sugar content, and anthocyanin accumulation than the unexposed side. It is concluded that sunlight increases red colour development of the mango exocarp by inducing PAL activity. Exposure to sunlight also enhances endogenous sugar accumulation in mango fruit. © 2011 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.